Pengaruh Musik Tradisional Gamelan Selonding Bali Mengurangi Kecemasan Lansia - Artana, I Wayan; Widiyani, Yunik; Dewi, Si Putu Agung Ayu Pertiwi (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2020)
Decreased physiological functions of various organ systems that occur in the elderly often result in anxietythat can interfere with other functions, including social functions and health. The anxiety that is nothandled properly can continue to be depressed even to commit suicide. This study aims to determineBalinese selonding gamelan music's effect on anxiety in the elderly in Banjar Selat, Buahan Kaja,Payangan, Gianyar. The design used was pre-experimental with one group pretest-posttest design.Sampling using purposive sampling totaling 41 older adults. Anxiety data were collected using theHamilton Rating Scale for Anxiety (HARS) in the analysis using the Wilcoxon Signed-Rank statistical testat a 95% confidence level (α 0.05). Statistical test results found p = 0.001, < 0.05. Statistically, there was asignificant influence on Balinese selonding gamelan music in reducing the elderly's anxiety. It wasrecommended to reduce the level of anxiety of the elderly, can apply Selonding gamelan music therapy.Keywords: anxiety, , elderly, gamelan Selonding